Alternating Release of Different Bioactive Molecules from a Complexation Polymer System - Jeon, J.H. (2008)
Regeneration of bone is driven by the action of numerous biomolecules. However, most osteobiologic devices mainly depend on delivery of a single molecule. The present studies were directed at investigating a polymeric system that enables localized, alternating delivery of two or more biomolecules. The osteotropic biomolecules studied were simvastatin hydroxyacid (Sim) and parathyroid hormone (1-34) (PTH(1-34)), and the antimicrobial peptide cecropin B (CB) was also incorporated. Loaded microspheres were made using the complexation polymer system of cellulose acetate phthalate and Pluronic F-127 (blend ratio, 7:3). By alternating layers of the different types of microspheres, 10-layer devices were made to release CB and Sim, CB and PTH, or Sim and PTH. In vitro experiments showed five discrete peaks for each molecule over a release period of approximately two weeks. MC3T3-E1 osteoblastic cells alternately exposed to the osteotropic biomolecules showed enhanced proliferation and early osteoblastic activity. Alternating delivery of 10 nM Sim and either 500 pg/ml or 5 ng/ml PTH showed additive effects compared to the CB/Sim or CB/PTH devices. These implantable formulations may be useful for alternating delivery of different biomolecules to stimulate concurrent biological effects in focal tissue regeneration applications.